When calls the heart. Complete season 6 [videorecording (DVD)] - Krakow, Erin; Wagner, Jack, 1959-; Loughlin, Lori; Cummins, Martin, 1969-; Hutton, Pascale; Smith, Kavan, 1970-; Greene, Paul, 1974- (EdifyFilms, 2019)
Follow the adventures of a young school teacher as she faces new adventures and trials with the many citizens of Hope Valley, on the Canadian frontier.